2020
DOI: 10.3390/cancers12103040
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Stem-Like Cells Can Be Targeted in Boron Neutron Capture Therapy with Boronophenylalanine

Abstract: As glioma stem cells are chemo- and radio-resistant, they could be the origins of recurrent malignant glioma. Boron neutron capture therapy (BNCT) is a tumor-selective particle radiation therapy. 10B(n,α)7Li capture reaction produces alpha particles whose short paths (5–9 µm) lead to selective killing of tumor cells. P-boronophenylalanine (BPA) is a chemical compound used in clinical trials for BNCT. Here, we used mass cytometry (Cytof) to investigate whether glioma stem-like cells (GSLCs) take up BPA or not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…It has been revealed that the repurposing of antipsychotic drugs, such as haloperidol [ 104 ] and phenothiazine [ 105 ], may be a viable alternative for the treatment of CNSMs. Another recent report utilizing Mass Cytometry, revealed the selective targeting of glioma stem cells (characterized as CD98 + cells coexpressing stem cell markers, including Oct3/4, Nestin, SOX2, Musashi-1, PDGFRα, Notch2, Nanog, STAT3 and C-myc) by P-boronophenylalanine (BPA), a chemical compound used in Boron neutron capture therapy [ 106 ].…”
Section: Flow Cytometry For Study Of Anticancer Agent Efficacymentioning
confidence: 99%
“…It has been revealed that the repurposing of antipsychotic drugs, such as haloperidol [ 104 ] and phenothiazine [ 105 ], may be a viable alternative for the treatment of CNSMs. Another recent report utilizing Mass Cytometry, revealed the selective targeting of glioma stem cells (characterized as CD98 + cells coexpressing stem cell markers, including Oct3/4, Nestin, SOX2, Musashi-1, PDGFRα, Notch2, Nanog, STAT3 and C-myc) by P-boronophenylalanine (BPA), a chemical compound used in Boron neutron capture therapy [ 106 ].…”
Section: Flow Cytometry For Study Of Anticancer Agent Efficacymentioning
confidence: 99%
“…All the stable isotopes of exogenous cellular elements across the mass range from 75 to 209 Da can be applied as reporters for CyTOF, which shows minimal spectral overlap and requires no compensation between detection channels. [ 5 ] To date, various metal isotopes, including yttrium (Y), [ 6 ] silver (Ag), [ 7 ] cadmium (Cd), [ 8 ] indium (In), [ 9 ] lanthanide elements (Ln, from La to Lu, except Pm), [ 10 ] tantalum (Ta), [ 11 ] and bismuth (Bi) [ 12 ] have been investigated for protein analysis (identity, function, modification, expression level), while tellurium (Te), [ 13 ] ruthenium (Ru), [ 14,15 ] rhodium (Rh), [ 16 ] iridium (Ir), [ 16 ] palladium (Pd), [ 17 ] osmium (Os), [ 15 ] iodine (I), [ 18 ] platinum (Pt) [ 19 ] have been tested for cell identification (nucleus, viability, cell cycle, cell barcode). In order to site‐specifically attach metal cations to an antibody for biomarker detection, elemental labeling strategies based on polymer and nanoparticles (NPs) have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Being rather resistant to γ-photons and X-rays, CSCs are more sensitive to the cytotoxic action of neutrons [ 286 ], protons [ 287 , 288 , 289 ] and α-particles [ 290 , 291 ]. In contrast to photon radiation, which may induce the EMT and increase the fraction of CSC-like cells in target tumors [ 142 , 292 ], proton beams appear to reduce both the cell migration ability and amounts of CSC-like cells in irradiated tumor cell populations, as was demonstrated for non-small cell lung carcinoma A549 cells exposed to proton irradiation [ 288 ].…”
Section: Hypoxia-induced Generation Of Radioresistant Csc-like Celmentioning
confidence: 99%
“…Besides proton beams, therapy with α-particles was also suggested as a curative modality to target prostate CSCs [ 290 ] and glioma stem cells [ 291 ]. In turn, carbon ion irradiation has been suggested as a promising approach to the eradication of CSCs [ 295 ] and/or suppression of their migration/invasiveness [ 296 , 297 ].…”
Section: Hypoxia-induced Generation Of Radioresistant Csc-like Celmentioning
confidence: 99%